2022
DOI: 10.1080/10717544.2022.2092235
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of the novel structure curcumin derivative–loaded solid lipid nanoparticles: synthesis, optimization, characterization and anti-tumor activity screening in vitro

Abstract: This study investigated the effect of structural modification of Curcumin (CU) combined with the solid lipid nanoparticles (SLN) drug delivery system on anti-tumor activity in vitro . A new structure of Curcumin derivative (CU1) was successfully synthesized by modifying the phenolic hydroxyl group of CU. CU1 was two times more stable than CU at 45 °C or constant light. The SLN containing CU1 (CU1-SLN) was prepared, and the particle size, polydispersity index, entrapment efficiency, drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In recent years, the antitumor effect of CUR has attracted attention. Some studies have found that CUR can prevent tumor angiogenesis and cell proliferation, induce cancer cell apoptosis, downregulate epidermal growth factor receptor (EGFR) activity and human epidermal growth factor receptor 2 (HER2) expression levels, downregulate nuclear transcription factor, inhibit the activation of the STAT3 signaling pathway, downregulate the expression level of cyclooxygenase 2 (COX-2), and reduce the synthesis level of MMP9 and inducible nitric oxide synthase (iNOS), thus exerting its antitumor effect through multiple pathways [ 14 , 15 ]. However, the application of CUR is constrained by its low water solubility, ease of aqueous solution hydrolysis, clear first-pass elimination effect and low bioavailability [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the antitumor effect of CUR has attracted attention. Some studies have found that CUR can prevent tumor angiogenesis and cell proliferation, induce cancer cell apoptosis, downregulate epidermal growth factor receptor (EGFR) activity and human epidermal growth factor receptor 2 (HER2) expression levels, downregulate nuclear transcription factor, inhibit the activation of the STAT3 signaling pathway, downregulate the expression level of cyclooxygenase 2 (COX-2), and reduce the synthesis level of MMP9 and inducible nitric oxide synthase (iNOS), thus exerting its antitumor effect through multiple pathways [ 14 , 15 ]. However, the application of CUR is constrained by its low water solubility, ease of aqueous solution hydrolysis, clear first-pass elimination effect and low bioavailability [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor therapy that targets the Hippo-YAP signaling pathway has gained popularity in recent years. YAP-like peptides created by Zhou et al [ 14 ] have demonstrated their ability to inhibit tumor growth in primary liver cancer xenograft models. Our study indicates that WZ10 may decrease tumor activity in vitro through the Hippo-YAP pathway, induce cell apoptosis and limit cell proliferation and invasion, supporting WZ10 as a promising medication for the therapeutic treatment of ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The encapsulation efficiency was calculated as the difference between the added content of coumarin-6 and the content in the supernatant. 15 …”
Section: Methodsmentioning
confidence: 99%
“…The encapsulation efficiency was calculated as the difference between the added content of coumarin-6 and the content in the supernatant. 15 Coumarin 6 release from DFPs was determined by suspending DFPs in Hank's balanced salt solution (HBSS, 2.0 mL) at pH 7.2. The suspension was placed in a dialysis bag (molecular weight cutoff=5000 Da), followed by immersion in another 20.0 mL HBSS at 37°C with agitation at a constant speed of 100 r/min.…”
Section: Preparation and Characterization Of Dfpsmentioning
confidence: 99%
“…Results showed improved bioavailability and inhibitory effects as compared to CU. [ 156 ] Furthermore, a combinational strategy was employed to utilize a multi‐drug‐loaded SLN with PTX and CU in a lung cancer xenograft tumor model, and the findings revealed high clinical therapeutic potential for lung cancer therapies. [ 157 ] However, these studies utilized NPs to be passively targeted.…”
Section: Smart Lipid‐based Nanocarriersmentioning
confidence: 99%